Strength of three-sheet spot welds with critical nugget sizes in tensile shear, cross tension, peel and fatigue tests. (May 2022) - Siimut, K; Zwicker, MFR; Nielsen, CV
Plug failures have been observed in three-sheet spot welds, where the weld nugget did not penetrate into the outer sheet. Such solid-state bonds were found to be formed as a result of high contact pressure and temperature during welding. The strength of single spot welds was studied in a three-sheet combination (0.61 mm DX54 on two 1.21 mm DP600) with nugget penetrations into the thin sheet below 40%. The static strength was evaluated by tensile shear, cross tension and mechanized peel testing, and fatigue tests were carried out in tensile shear configuration at 30 Hz and mean load of 2 kN. It was found that loading of the specimens in tensile shear, mechanized peel and cross tension tests leads to a plug failure and a ductile fracture of the thin sheet. The weld strength is not correlated with the nugget penetration into the thin sheet but is determined by the area of the bonded interface, instead, as shown by peel and cross tension tests. Fatigue tests revealed that the specimens break by a plug failure. The failure mechanism was found to be ductile for the highest load range after approximately 33 000 cycles. At lower load ranges, evidence of a crack was found in the DX54 sheet, leading to higher stress concentration and subsequent ductile fracture. It was estimated that a load range of 940 N leads to failure after approximately 10 6 cycles.